2002
DOI: 10.1161/01.cir.0000023555.38685.5b
|View full text |Cite
|
Sign up to set email alerts
|

Potentiated Sympathetic Nervous and Renin-Angiotensin Systems Reduce Nonlinear Correlation Between Sympathetic Activity and Blood Pressure in Conscious Spontaneously Hypertensive Rats

Abstract: Background-Patients with a reduced nonlinear component of heart rate regulation have a poorer outcome. Methods and Results-We investigated whether a nonlinear correlation between renal sympathetic nerve activity (RSNA) and blood pressure or renal blood flow is reduced in conscious, spontaneously hypertensive rats (SHR) by comparing them with normotensive Wistar-Kyoto rats (WKY). We also determined the linearity and nonlinearity of the correlation in SHR who were given an angiotensin II receptor blocker, cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 30 publications
1
30
0
1
Order By: Relevance
“…25) mg kg À1 per day) than those in the present study (2 mg kg À1 per day). However, Sakata et al 28 demonstrated that 1 mg kg À1 per day of CAN for 2 weeks causes sympathoinhibition in SHR. Although blood pressure of SHRs in their study is lower than that of the SHRSPs in the present study, and the heart rate of the SHRs were similar to that of the WKY rats in their study, these previous studies suggested that the difference in sympathoinhibition between TLM and CAN in the present study may not be due to the dose of CAN.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…25) mg kg À1 per day) than those in the present study (2 mg kg À1 per day). However, Sakata et al 28 demonstrated that 1 mg kg À1 per day of CAN for 2 weeks causes sympathoinhibition in SHR. Although blood pressure of SHRs in their study is lower than that of the SHRSPs in the present study, and the heart rate of the SHRs were similar to that of the WKY rats in their study, these previous studies suggested that the difference in sympathoinhibition between TLM and CAN in the present study may not be due to the dose of CAN.…”
Section: Discussionmentioning
confidence: 99%
“…15,[18][19][20] Peripherally administered ARBs also inhibit the central actions of angiotensin II in the brain. [21][22][23][24][25][26][27][28] Furthermore, we demonstrated that orally administered TLM inhibits SNS activation by reducing oxidative stress in the brains of hypertensive rats. 16 However, it has not been determined whether the sympathoinhibition caused by orally administered ARBs is a class effect of ARBs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We sought to make a mathematical model of the system that meets the three experimental findings: 1) the SNA peaks precede the HR peaks and BP nadirs 24 , 2) the power spectra of the HR shows a 1/f-like relationship between frequency and power 19,20 , and 3) the HR exhibits low-order chaos 18 . Based on the conclusion that our system of interest is chaotic in nature, we modeled the system after a known chaotic electrical circuit, the Chua circuit 25,26 .…”
Section: Mathematical Model Of Hr Dynamicsmentioning
confidence: 99%